Astrocytic and microglial cell functions in neuroinflammatory diseases and their animal models - Hashimoto, Kei; Gotoh, Mari; Ikeshima-Kataoka, Hiroko (Frontiers in Cellular Neuroscience, 2025)
Neurodegenerative diseases are frequently accompanied by inflammatory responses and alterations in lipid metabolism, both of which are believed to negatively affect neural regeneration in mammals. In addition to immune cells, glial cells such as astrocytes and microglia contribute significantly to these inflammatory processes, and it is now recognized that lipid droplet accumulation and cholesterol metabolism are dysregulated in these glial cells. Consequently, recent studies have examined inflammation and lipid metabolism from the standpoint of glial cell function; however, effective therapeutic strategies remain unestablished. By contrast, in zebrafish, a teleost species, robust neural regeneration occurs within a short period after injury to the telencephalon or spinal cord. In this review, we aimed to identify candidate functional factors by comparing mouse and zebrafish disease models and to explore molecules with potential therapeutic relevance for mammalian neurological disorders.